Direct Electrochemistry of Glucose Oxidase at Reduced Graphene Oxide and β‐Cyclodextrin Composite Modified Electrode and Application for Glucose Biosensing. Issue 10 (26th June 2015) - Palanisamy, Selvakumar; Devasenathipathy, Rajkumar; Chen, Shen‐Ming; Ajmal Ali, M.; Karuppiah, Chelladurai; Balakumar, V.; Prakash, P.; Elshikh, Mohamed S.; Al‐Hemaid, Fahad M. A.
Abstract A simple glucose biosensor has been developed based on direct electrochemistry of glucose oxidase (GOx) immobilized on the reduced graphene oxide (RGO) and β‐cyclodextrin (CD) composite. A well‐defined redox couple of GOx appears with a formal potential of ∼−0.459 V at RGO/CD composite. A heterogeneous electron transfer rate constant (Ks) has been calculated for GOx at RGO/CD as 3.8 s−1. The fabricated biosensor displays a wide response to glucose in the linear concentrations range from 50 µM to 3.0 mM. The sensitivity and limit of detection of the biosensor is estimated as 59.74 µA mM−1 cm−2 and 12 µM, respectively.